BUSINESS RISK, FINANCIAL RISK AND FIRM PERFORMANCE AN EMPIRICAL STUDY OF INDONESIAN MANUFACTURING SECTOR - Utami Prasetiawati (Jurnal Ekonomi dan Bisnis Airlangga, 2019)
Introduction: This paper empirically examines the impact of degree of operating leverage (DOL) and degree of financial leverage (DFL) to firm performance by using size as control variable. Firm performances used are return on equity (ROE) and market to book ratio (MTB).Methods: Statistical tool used is pooled regression while sample used is all Indonesian manufacturing firms listed in Indonesia Stock Exchange from 2009-2013.Results: The findings revealed that high fixed asset firms pose higher DOL compared to those of lower ones; and highly financial leveraged firms pose significantly higher DFL compared to those of lower financial leveraged ones. Further, both DOL and DFL impacting ROE in negative manner but only DOL is statistically significant, while all variables (DOL, DFL and Size) impacting MTB in negative manner but only size is statistically significant.Conclusion and suggestion: The finding shows that Indonesian stock market investors do not regard risks as important elements in making investment decisions. The findings, however, pose a quite low R squared value of 1.39% for ROE and 2.4% for MTB. This means only those percentage of ROE and MTB can be explained from the variables used in this research. Thus, the author encourge more variables should be included in the future research, including macro economic variables, as it is one of the key component in firm performance.